1997
DOI: 10.1016/s0741-5214(97)70099-5
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and management of venous aneurysms

Abstract: Venous aneurysms are unusual vascular malformations that occur equally between the sexes and are seen at any age. Most patients have a painful mass of the extremity, and diagnosis is achieved by radiologic examination. Superficial venous aneurysms of the inguinal region are often misdiagnosed. Thromboembolism is more common in aneurysms involving the deep venous system. Because of their potential morbidity, management should be surgical in the majority of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
227
0
12

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(241 citation statements)
references
References 35 publications
(2 reference statements)
2
227
0
12
Order By: Relevance
“…They should be recognized as causes of the potential complications inherent to this pathology, such as deep venous thrombosis (DVT) and rupture and compression of adjacent structures. 6,7 The majority of venous aneurysms described in the literature are secondary to trauma, arteriovenous fistula or varicose disease. 6,8 No cases were found that specifically describe a relation to crutch use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They should be recognized as causes of the potential complications inherent to this pathology, such as deep venous thrombosis (DVT) and rupture and compression of adjacent structures. 6,7 The majority of venous aneurysms described in the literature are secondary to trauma, arteriovenous fistula or varicose disease. 6,8 No cases were found that specifically describe a relation to crutch use.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the venous aneurysms were asymptomatic in this case, they should be taken into consideration during differential diagnosis, given the potential for complications in patients who use crutches, especially those who develop DVT or pulmonary thromboembolism. 7 The conventional treatment for venous aneurysms in the lower limbs is surgical resection, because of the high rates of thromboembolic complications associated with them. 6,7 However, the definitive treatment for venous aneurysms in the upper extremities is much less well defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Histologic analysis shows vein wall fragmentation with degeneration of elastin. 8 Most of the authors advice only reassurance to the patients. The contralateral IJV in majority of these reported cases are normal.…”
Section: Case Reportmentioning
confidence: 99%
“…Por sua raridade, os aneurismas venosos são pouco descritos; há relatos esporádicos na literatura mundial. Em quatro grandes revisões, foram relatados 147 casos por Calligaro et al 4 , 311 por Schild et al 5 , 39 por Gillespie et al 6 .…”
Section: Introductionunclassified